2020
DOI: 10.32832/pkm-p.v4i1.721
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: ABSTRAKRancangan board games tentang Covid-19 dikembangkan dalam bentuk permainan yang tepat, merupakan salah satu alternatif media informasi dan edukasi bagi anak-anak. Pada masa pandemi ini pengumuman kasus pertama pasien virus corona Indonesia sempat menimbulkan kekhawatiran dalam berbagai sektor. Penyebaran informasi penanggulangan dan pencegahan Covid-19 saat ini menjadi sebuah kebutuhan bagi masyarakat, terutama bagi anak-anak yang menjadi sosok paling rentan, perlunya diadakan sebuah pemahaman tanggap b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…This can be seen based on the results of the effectiveness test which shows an increase in students' understanding of school objects and the human body. Learning playing will be very effective for early childhood learning because children will be more motivated when they know that they are currently playing, not learning (Nurhayati & Nurzaelani, 2020;Ratnawati & Asniawati, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be seen based on the results of the effectiveness test which shows an increase in students' understanding of school objects and the human body. Learning playing will be very effective for early childhood learning because children will be more motivated when they know that they are currently playing, not learning (Nurhayati & Nurzaelani, 2020;Ratnawati & Asniawati, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Another objective is to find out whether the APPED model can be used in the development of printed learning media or not. Some previous research related to the application of board games in the learning process is research from which states that the application of board games is very effective in the learning process for early childhood (Nurhayati & Nurzaelani, 2020). Previous research also found that there was an increase in students' abilities in the cognitive aspect by applying the board game method in the learning process (Maryanti et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Other research findings that show that there is no effect between ISR on banking performance are the research of Mosaid & Boutti (2012), Nurhayati & Rustiningrum (2021), Setiawan et al (2022, and Utomo & Azib (2019). This means that the number of ISR disclosure items disclosed by Islamic Commercial Banks cannot affect the performance of their sharia maqashid (Mosaid & Boutti, 2012).…”
Section: The Influence Of Islamic Social Reporting On the Maqashid Sh...mentioning
confidence: 98%
“…ISR is a collection of social responsibility reporting indicators set by AAOFII that are compliant with Sharia (Nurhayati & Rustiningrum, 2021) and further developed by researchers (Haniffa, 2002;Maali et al, 2006;Ousama andFatima, 2006 andOsman et al ., 2009). Retnaningsih et al (2019) found that ISR had an impact on the financial performance of the banking sector.…”
Section: The Influence Of Islamic Social Reporting On the Maqashid Sh...mentioning
confidence: 99%
“…Penggunaan media pada proses pembelajaran dinilai cukup efektif untuk meningkatkan kualitas pendidikan (Nugroho, 2021), hal ini karena penggunaan media dapat menciptakan suasana belajar yang menyenangkan, sehingga siswa dapat lebih mudah memahami materi yang diberikan (Prihandoko & Yunianta, 2021). Kebermanfaatan board game juga dapat digunakan oleh siswa dalam mempelajari dan mencari pengetahuan baru (Nurhayati & Nurzaelani, 2020), dan membantu siswa memahami materi pelajaran yang diberikan oleh guru (Nordin et al, 2022).…”
Section: Pendahuluanunclassified